2019
DOI: 10.1007/s11051-019-4583-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and sociological perspectives for good governance of sustainable nanotechnology development in Malaysia

Abstract: Nanotechnology is developed to improve public well-being, stimulate economic growth, and provide environmental solutions, which are essential for sustainable development. However, the uncertain risks of nanotechnology may destroy public confidence and impede nanotechnology development from facilitating sustainable development. Thus, public perception is a critical component to understand public acceptance of nanotechnology and for nanotechnology development to be well governed. Good governance of nanotechnolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Furthermore, nanotechnology enhances the shelf life of packaging while also improving food safety and downstream processes such as protein extraction of large molecular weight proteins such as bovine serum albumin. Aside from the tremendous lineup of nanotechnology applications in the food industry, Kamarulzaman et al (2019) reported in their study that nanotechnology is viewed as a key component of national economic development, with innovation in this field seen as holding significant potential for groundbreaking scientific advancements and improving overall human life quality. The contribution of nanotechnology is gradually increasing, and the entire nanotechnology market size and expected value in the food industry will be greater than RM1.31 (US$0.31) billion in 2025 (Dardak, 2023).…”
Section: Malaysia Nanotechnology Initiatives In Food Industrymentioning
confidence: 99%
“…Furthermore, nanotechnology enhances the shelf life of packaging while also improving food safety and downstream processes such as protein extraction of large molecular weight proteins such as bovine serum albumin. Aside from the tremendous lineup of nanotechnology applications in the food industry, Kamarulzaman et al (2019) reported in their study that nanotechnology is viewed as a key component of national economic development, with innovation in this field seen as holding significant potential for groundbreaking scientific advancements and improving overall human life quality. The contribution of nanotechnology is gradually increasing, and the entire nanotechnology market size and expected value in the food industry will be greater than RM1.31 (US$0.31) billion in 2025 (Dardak, 2023).…”
Section: Malaysia Nanotechnology Initiatives In Food Industrymentioning
confidence: 99%
“…158,159 This can be similarly observed in other parts of the world, where a large percentage of citizens know very little about nanotechnology. [160][161][162] On the other hand, countries such as China and Singapore demonstrated relatively high awareness of nanotechnology. 163,164 Public sentiments toward nanotechnology are generally positive and cautious.…”
Section: Environmental Impact and Life Cycle Of Nanotechnologymentioning
confidence: 99%